ISOLATION AND IDENTIFICATION OF FLAVONOID COMPOUND EXTRACTIRE ETHYL ACETATE FRACTION EXTRACTED FROM THE RHIZOMES FINGERROOT OF (Boesenbergia pandurata (Roxb.) Schlecht) (Zingiberaceae) - Ochtavia Prima Sari; Titik Taufiqurrohmah (Indonesian Journal of Chemistry, 2006)
Boesenbergia pandurata (Roxb.) Schlecht is one of fingerroot plant in ginger family (Zingiberaceae). The rhizomes of the plant contained a lot of secondary metabolites compounds. Therefore, the purpose of the research is to isolate and identify the flavonoid compound from the plant. The rhizomes were extracted with metanol continued by partition using ethyl acetate-water (1:1). The ethyl acetate extract was chromatographed on a column of Si gel (Vacuum Liquid Chromatography and Gravitation Column Chromatography) using n-hexane-ethyl acetate (5:2) as eluents. Further purification by recristalization  using benzene  produced a compound as yellow powder (16 mg) having melting point of 294-295 oC. The spectra of isolated compound were determined by spectroscopic UV-Vis, FT-IR, and GC-MS. Spectrum UV-Vis of the isolated compound showed ultraviolet absorption at λmax (MeOH, nm) 290 and 322; λmax (MeOH+NaOH, nm) 322; λmax (MeOH+AlCl3, nm) 309; λmax (MeOH+AlCl3+HCl, nm) 310; λmax (MeOH+NaOAc, nm) 322 and λmax (MeOH+NaOAc+H3BO3, nm) 290. Its FT-IR spectrum represented a number of absorption lied on νmax (cm-1) : 3142.5; 3012.6; 2893; 2345.3; 1631.7; 1585.4; 1357.8; 1168.8; and 825.5. GC-MS spectrum of the isolated compound exhibited an [M]+ ion peak at m/z = 256 with retention time of  22,579. Based on the results of spectrum analysis it can be concluded that the compound is 5,7-dyhydroxyflavanone.